Pharmacist prescriber implementation in the experiences of general practitioners, pharmacist prescribers and patients: qualitative study based on pilot trial in Slovenia - Stuhec, Matej; Kovacic, Alenka; Korpar, Marjetka; Banovic Koscak, Ana; Koder, Barbara; Mahoric, Dunja; Bernik Golubic, Spela; Homar, Vesna; Stepanovic, Aleksander; Rotar Pavlic, Danica; Gorup Cedilnik, Eva (Frontiers in Pharmacology, 2025)
IntroductionMedication review services have been nationally implemented in Slovenia, and a pilot program for pharmacist prescribing has already been conducted. Qualitative evidence is required to support its integration into healthcare systems.AimThe aim was to explore the experiences of general practitioners (GPs), patients, and clinical pharmacist prescribers regarding the national pilot trial and possible implementation of pharmacist prescribing in Slovenia.MethodsA qualitative study design using semi-structured interviews was applied. A working group developed and piloted the interview guide. Pharmacist prescribers, GPs, and patients involved in a pharmacist prescribing pilot trial in Slovenia were invited via email. Recruitment continued until data saturation was achieved. Purposive sampling was used for recruitment. Interviews were conducted between May and August 2025, recorded, and transcribed in MAXQDA. Data were analysed thematically using the Consolidated Framework for Implementation Research (CFIR). The research team agreed upon final coding. The COREQ (Consolidated Criteria for Reporting Qualitative Research) checklist was applied to ensure methodological rigour.ResultsSeventeen participants were interviewed: four pharmacist prescribers, five patients, and eight GPs. Across all groups, participants expressed positive experiences with integrating pharmacist prescribers into the Slovenian healthcare system. Patients valued enhanced monitoring by clinical pharmacists and perceived improved quality of prescribing and clinical outcomes. GPs highlighted effective collaboration, particularly through medication review, as a foundation for pharmacist prescribing. Pharmacist prescribers reported professional satisfaction with monitoring and prescribing responsibilities. GPs and pharmacist prescribers expressed satisfaction with the collaborative practice agreement (CPA) developed in Slovenia and considered dependent prescribing the most appropriate model for initial implementation. Reported barriers included the absence of legislation, reimbursement mechanisms, and structured education. Both pharmacist prescribers and GPs emphasised the need for additional competencies for pharmacist prescribers in Slovenia.ConclusionThis is the first qualitative study examining a pharmacist prescribing pilot outside Anglo-Saxon countries based on experiences from a real national pilot. Findings indicate positive experiences among stakeholders and support for implementation of pharmacist prescriber in Slovenia, with implications for broader applicability.